Coastal Development between Opportunity and Disaster Risk : A Multisectoral Risk Assessment for Vietnam - Braese, Johannes; De Vries Robbe, Sophie Anne; Rentschler, Jun (World Bank, Washington, DC, 2020)
This paper presents a multisectoral risk assessment, analyzing natural risks faced by key drivers of socioeconomic development in coastal Vietnam. The analysis quantifies the exposure of assets and economic activity to the following natural hazards: riverine flooding, coastal flooding, typhoon winds, coastal erosion, and saline intrusion. These hazards are analyzed according to their impact on agricultural production, aquaculture, human settlements, industrial zones, tourism, health care facilities, schools, and the electricity transmission network. Overall, the results show the complex nature of natural risk in Vietnam, with significant exposure of key economic sectors, public services and assets. The estimates suggest that exposure varies greatly between hazards, sectors, and provinces. This paper provides detailed technical descriptions of the methodologies, data sources, and analytical assumptions employed to obtain the estimates, and acts as a technical background paper to Resilient Shores: Vietnam's Coastal Development between Opportunity and Disaster Risk (Rentschler et al., 2020).